Matter accumulation and photosynthetic responses of macaw palm to cyclical drought - Mota, Clenilso Sehnen; Cano, Marco Antonio Oliva (Revista Caatinga, 2016)
The objective of this work was to evaluate the plant-water relations, photosynthetic parameters and growth of macaw (Acrocomia aculeata (Jacp.) Lodd. ex Mart.) plants, thus, ten plants were subjected to three successive drought and rehydration cycles and ten other plants were irrigated normally as control. The drought cycles consisted of a suspension of irrigation until the net CO2 assimilation rate (A) reach values lower than 5% of the control, and a rehydration until a plants recover at least 85% of A of the control plants. Reductions in A, stomatal conductance (gs ) and transpiration (E), above 95%, were found with predawn leaf water potential (Ψpd) of -1.85 MPa. After rehydration, the gs and E of plants with and without water stress was not different, however, A presented a significant difference. Leaf water potentials below -0.5 MPa reduced the intracellular and atmospheric CO2 ratio and increased water use efficiency, and values of -1.85 MPa, when both showed an increase and decrease, respectively. The reduction of A and gs was linear and proportional to Ψpd. Total dry matter accumulation reduced by 50% in the plants subjected to drought. The cyclic water stress resulted in reduction of gas exchange and matter accumulation in macaw palm plants; a stomatal limitation of A occurred until Ψpd of -1.85 MPa, and then a non-stomatal limitation.

Com o objetivo de avaliar as relações hídricas, parâmetros fotossintéticos e crescimento em plantas de macaúba, dez plantas foram submetidas a três ciclos sucessivos de seca/recuperação e outras dez irrigadas normalmente como controle. Cada ciclo consistiu em suspender a irrigação até que a assimilação liquida de CO2 (A) fosse inferior a 5% em relação às plantas controle, momento esse de retomada da irrigação até que A recuperasse no mínimo 85% em relação ao controle. Reduções de A, condutância estomática (gs ) e transpiração (E), acima de 95%, foram obtidas em Ψam de -1.85 MPa. Após a reidratação, gs e E não apresentaram diferenças entre as plantas sem e com deficiência hídrica, diferentemente do que ocorreu com A. Potencial hídrico foliar abaixo de -0,5 MPa promoveu redução da relação entre concentração intercelular e atmosférica de CO2 e aumento do uso eficiente da água, até valores de -1.85 MPa, quando ambos apresentaram elevação e redução, respectivamente. A redução de A e gs foi linear e proporcional à de Ψam. O acúmulo de massa seca total foi reduzida em 50% pela imposição da seca. O estresse hídrico cíclico resultou em redução das trocas gasosas e de acúmulo da massa em macaúba, a limitação estomática de A atuou até Ψam de -1.85 MPa, quando passou a atuar a não estomática.
Keywords: Acrocomia aculeata; Photosynthesis; Water use efficiency; Plant- water relations; Fotossíntese; Eficiência no uso da água; Relações hídricas